GROUND BASED SUPPORT OF THE SPACE MISSION PARKER PERFORMED WITH UKRAINIAN LOW FREQUENCY RADIO TELESCOPES - V. V. Dorovsky; V. M. Melnik; A. I. Brazhenko (Radio Physics and Radio Astronomy, 2023)
Subject and Purpose. The sporadic radio emissions coming from the Sun in a broad frequency range contain a lot of important information concerning the solar corona, parameters of the radio frequency sources therein, and the parameter variations resulting from active processes on and about the Sun. These have been the reasons for recent launches of the space missions intended for stud- ying the Sun and its corona, such as the Parker Solar Probe (PSP) and the Solar Orbiter. The present work is aimed at demonstrating effectiveness of the ground-based support for the space missions, the PSP before all, which is provided by the large Ukrainian radio telescopes of the decameter wavelength range. Another purpose has been cross-calibration of the space-borne radiometer against calibrated data from a ground-based instrument.